Influence of Electrolyte Compositions and Electrical Parameters on Thermal Properties of Micro-Arc Oxidized AZ91 Alloy - Selvi, Ekin; Muhaffel, Faiz; Yurekturk, Yakup; Vanli, Ali Serdar; Baydogan, Murat (SPRINGER, 2022)
In this study, AZ91 Mg alloy was micro-arc oxidized using different voltages in silicate- and aluminate/phosphate-based (dual) electrolytes that included K2ZrF6 or Na2ZrO3 as the Zr source for synthesizing ZrO2 in the micro-arc oxidation (MAO) coatings. Structural characterizations were done by using scanning electron microscopy and x-ray diffraction techniques. MAO coating characteristics of different samples were compared by measuring coating thickness, surface roughness, average pore size, and total pore fraction. Both hardness and pull-off tests were conducted to characterize the mechanical properties of the coatings. Thermal conductivity measurements and thermal shock tests were also carried out to evaluate the effect of the electrolyte composition and the type of Zr containing compound. It was found that the equivalent thermal conductivity of the MAOed samples can be reduced up to 30% compared to the bare AZ91 alloy. The decrease of the thermal conductivity was mainly attributed to formation of a thicker and denser MAO coating, and the incorporation of ZrO2 phase into the fabricated MAO coating. Finally, increased thermal shock resistance was strongly correlated with a lower hardness and higher cohesive strength of the MAO coating, which also leads to smaller crack formation and spallation-free surface characteristics.
Keywords: magnesium alloy; micro-arc oxidation; thermal properties; zirconium; OXIDATION COATINGS; CORROSION-RESISTANCE; OXIDE COATINGS; DUTY CYCLE; CP TI; MAGNESIUM; PEO; BEHAVIOR; CONDUCTIVITY; PERFORMANCE; Materials Science